A preliminary report on newborn screening of inborn metabolic disorders - Tiwari, Abhishek Kumar; Bandyopadhyay, Debashish; Saha, Bijan (Indian Journal of Child Health, 2019)
Background: Newborn screening (NBS) for metabolic and genetic disorders, which can be treated or modified if detected early in life, can help to prevent potentially disastrous consequences and save a precious life. However, there is no nationwide consensus on neonatal screening in India; hence, several treatable cases may be missed. Objective: The objective of this study was to detect the prevalence of selected metabolic disorders among neonates and to diagnose them as early as possible to minimize the morbidity and mortality. Materials and Methods: This prospective study included all live newborns delivered during period 2015–2016 in a tertiary care neonatal unit in Kolkata. On the 3rd day of life, newborns were subjected to detailed history, with special emphasis on family history and history of consanguinity. This was followed by thorough clinical examination and metabolic screening for congenital hypothyroidism (CH), G6PD deficiency, phenylketonuria (PKU), congenital adrenal hyperplasia (CAH), galactosemia, and cystic fibrosis with heel prick blood sample collected on blotting paper. Results: Of 1373 babies, four babies were screened positive of CH, G6PD deficiency, CAH, and PKU, respectively. However, confirmatory test for PKU came out to be negative. Conclusion: NBS can be an important preventive public health program. Application of tandem mass spectrometry to newborn screening for metabolic disorders offers rapid results and covers a wide range of disorders. However, the screen-positive tests need to be confirmed by actual enzyme assay (for deficiency), chromatography/mass spectroscopy analysis, or DNA testing.